2015
DOI: 10.1186/s12879-015-1151-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the rapid urine lipoarabinomannan test for pulmonary tuberculosis among HIV-infected adults in Ghana–findings from the DETECT HIV-TB study

Abstract: BackgroundRapid diagnostic tests are urgently needed to mitigate HIV-associated tuberculosis (TB) mortality. We evaluated diagnostic accuracy of the rapid urine lipoarabinomannan (LAM) test for pulmonary TB and assessed the effect of a two-sample strategy.MethodsHIV-infected adults eligible for antiretroviral therapy were prospectively enrolled from Korle-Bu Teaching Hospital in Ghana and followed for minimum 6 months. We applied the LAM test on urine collected as a spot and early morning sample. Diagnostic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 42 publications
6
70
0
Order By: Relevance
“…The LAM test has been proven to be incredibly helpful in probable TB patients with negative smear results who are co-infected with HIV. The data from this study corroborate the diagnostic sensitivity of the urine LAM test, which was reported to be between 44% and 63% in hospitalized HIV-positive patients in South Africa and Uganda (Fielding et al, 2015;Lawn et al, 2013;Seddiki et al, 2014;Bjerrum et al, 2015;Shah et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The LAM test has been proven to be incredibly helpful in probable TB patients with negative smear results who are co-infected with HIV. The data from this study corroborate the diagnostic sensitivity of the urine LAM test, which was reported to be between 44% and 63% in hospitalized HIV-positive patients in South Africa and Uganda (Fielding et al, 2015;Lawn et al, 2013;Seddiki et al, 2014;Bjerrum et al, 2015;Shah et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…This was a prospective observational study of HIV‐infected individuals enrolled between January 2013 and March 2014 with 6 months of follow‐up. The study is based on data from a recently reported diagnostic accuracy study of the rapid urine lipoarabinomannan (LAM) test for TB diagnosis in Ghana . In brief, the study was conducted at the Fevers Unit, Korle‐Bu Teaching Hospital in the capital city of Accra.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular testing using the Cepheid GeneXpert® MTB/RIF is increasing in high disease burden areas[13,25,26], and has been evaluated using urine samples [13,27,28] but sensitivity is variable, particularly among HIV-infected patients [21,25,26,29]. But implementation of GeneXpert has been limited by cartridge stock-outs, the need for a continuous electricity, temperature control during specimen transport, as well as human resource limitations [16,3032].…”
Section: Discussionmentioning
confidence: 99%